The effectiveness of using the scattering strategy in developing values in social studies for sixth graders in the Kingdom of Saudi Arabia - Al-Dahesh, Faten Abdullah (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the effectiveness of using the diaspora combination strategy in developing values in social studies for sixth graders in the Kingdom of Saudi Arabia. The sixth primary from Jeddah Model School for Girls, the study adopted the quasi-experimental approach. Among the most important findings of the study, there are statistically significant differences at the level of moral significance (as0.05) between the mean scores of the students of the study group and the comparison group in the post application of the values scale in favor of Experimental group students. In light of the findings of the study, it recommends the following: Employing diaspora harmony in teaching social studies, and holding meetings, seminars and workshops for teachers on the importance of the effectiveness of diaspora harmony in teaching social studies and identifying how to employ it, and its importance, strengthening social studies books in the basic stage values to develop values for students. In light of the study results and recommendations, the researcher suggests the following: Conducting a similar study in social studies at different educational levels.